Internal jugular vein catheterization: A comparison between ultrasound guided technique with landmark guided technique - Singh, Shashi Ram; Yadav, Rajesh; Keyal, Niraj Kumar; Pathak, Vipul Vivek (Med Phoenix, 2022)
Introduction: Central venous cannulation is frequently performed procedures to gain access to the central vein. With increased use of ultrasonography to guide cannulation, the success rate has improved and it has decreased the time required for cannulation and complications. The aim of the study was to compare ultrasound guided technique (USG) and landmark technique (LMG) in Internal jugular vein. Materials and Methods: This study was conducted in National Medical College and Teaching Hospital, Birgunj from July 2019 to July 2020. Ethical clearance (NMC/420/075/076) was obtained from institutional review committee of NMC Birgunj. Total of 60 patients were randomly allocated into two groups; ultrasound group (USG) landmark group (LMG) underwent landmark guided catheterization. Access time, number of attempts for successful cannulation and incidence of various complications were compared between groups. Data analysis was done with Statistical Package for Social Science version 22. Result: The study was conducted on 60 patients, divided randomly into two groups with 30 patients in each group. The mean age for LMG was 48.57±16.08 years and for USG was 50.03±13.36 years. Out of 60 patients, 61.7% were male and 38.3% were female. The mean of neck dimension for LMG and USG was 35.95±6.327 and 35.67±6.194 cm respectively. The mean distance under LMG and USG was 19.07±1.780 and 18.33±2.368 cm respectively. The mean access time taken for LMG and USG was 403.10±98.111 and 217.57±75.408 seconds respectively (p<0.001). LMG technique showed total 5 cases (16.7%) of carotid artery puncture during procedure whereas there were no cases seen in USG (p value 0.05). Conclusion: This study has shown better result of ultrasound guided internal jugular cannulation when compared with landmark guided internal jugular vein cannulation technique by decreasing number of needle passes, access time, complication and giving least discomfort to the patient.